Farinhas de resíduos do processamento da tilápia do Nilo: composição centesimal e digestibilidade aparente da energia e nutrientes - Cardoso, Matheus dos Santos (2017)
The aim of the study was to evaluate the chemical, energy, and macro and micromineral composition of six fish meal from Nile tilapia processing waste of the different origins, as well as the determination of the apparent digestibility coefficients (ADC) of their nutrients, Energy and available phosphorus (PD) by juveniles of Nile tilapia. Six companies that manufacture fish meal from Nile tilapia processing residues were selected, four located in the Northwest region of São Paulo and two in the West of Paraná. Was analyzed centesimal composition of: dry matter (DM); Crude protein (CP); Gross energy (GE); Ethereal extract (EE); Crude fiber (CF) and; Mineral matter (MM); of macrominerals: phosphorus (P); Calcium (Ca) and magnesium (Mg); and microminerals: iron (Fe); Zinc (Zn); Copper (Cu) and manganese (Mn) of the flours. For the apparent digestibility trial, 196 tilapias weighing 76 ± 14g were distributed in a randomized block design in 14 conical cylindrical tanks with a useful volume of 500 L of water with a coupled feces collector system. The indirect method of fecal collection using 0.1% chromium oxide III (Cr2O3) as an inert marker was followed. The treatments consisted of a reference diet and six tests composed of 70% of the reference diet and 30% of the tilapia meal of different origins. The values of the nutrients and the energy of the tilapia meal showed variations: DM between 94.44% and 97.76%; CP from 54.73% to 60.41%; GE between 4368 and 4755 kcal. Kg-1; EE between 9.27% and 15.48%; CF from 4.22% to 6.22% e; MM between 22.23% and 27.19%. The content of macro and microminerals presented variations: for P between 4.17% and 4.66%; Ca between 7.17% and 9.78%; Mg between 0.112 to 0.193 mg. kg-1; Fe ratio of 173.18 to 830.45 mg. kg-1; Zn from 17.97 to 55.01 mg. kg-1; Cu between 2.82 and 9.90 mg. kg-1 and Mn between 12.08 and 26.75 mg. kg-1. Significant differences (P <0.05) were observed for ADCMS, which presented values ranging from 58.37% to 74.43% and ADCCP values ranging from 88.37% to 92.89%. No differences were observed for ADCGE, which presented a mean of 84.67%, ADCEE of 84.92% and PD of 25.99%.The fishmeal from of the the Nile tilapia processing waste of the different industries showed variations in their nutritional values, however, no differences were observed in their biological values that would compromise their use in tilapia diets.